Про осіле населення понизь Дніпра та Південного Бугу у X—XIII ст. - Буйських, С.Б.; Ієвлєв, М.М. (Археологія, 1991)
У статті на основі нових археологічних матеріалів та з залученням писемних джерел досліджується питання про осіле населення понизь Дніпра та Південного Бугу — району постійного суперництва Давньої Русі та Візантії X—XIII ст. Проблема существования оседлого населения в низовьях Днепра и Южного Буга в период образования и расцвета Киевской Руси (X—ХIII вв.) — одна из сложнейших и до конца не решенных в отечественной науке. В литературе, на основании некоторых сообщений письменных источников, высказывались предположения о существовании в X—XI вв. в устье Днепра, за которое вели постоянную борьбу Византия и Русь, оседлых греческих (херсонесских) и древнерусских поселений. Однако достаточно ярких памятников, подтвердивших бы это, до недавнего времени в регионе не было.
В определенной степени лакуну в этом вопросе и заполняют материалы, полученные в ходе раскопок 1982 г. двух новых поселений X—XIII вв. Аджигол-1 и Днепровское-2, открытых на побережье Днепро-Бугского лимана, чему и посвящена данная статья. Близость общего облика культуры поселений с древнерусскими памятниками Степного Поднестровья позволяет связывать их возникновение с продвижением уличей на юг по Днепру в X в. В дальнейшем (XI—XIII вв.) состав их жителей, как и других оседлых памятников низовий Днепра, по-видимому, пополнялся новыми переселенцами из Среднего Поднепровья. В XI—XII вв. на базе одного из этих поселений возник древнерусский город Олешье. A problem on existence of settled population in the Lower Dnieper and South Bug in the period of formation and flourishing of the Kiev Rus (I0th-13th cent) is one of the most intricate and still undecided problems of the home science. Proceeding from information found in some written sources certain assumptions were advanced in literature concerning existence of settled Greek (the Chersonese) and Old Rus settlements in the Dnieper mouth in the 10th-11th cent which was a constant bone of contention for Byzantium and Rus. However, till recently there were no sufficiently reliable evidence in the region to confirm that.
This gap is, to a definite extent, filled by data obtained during excavations of two new settlements of the 10th-13th cent. (Adjigol-1 and Dneprovskoe-2) discovered on the Dnieper-Bug estuary coast in 1982 and described in the paper. Proximity of the general aspect of culture of those settlements with Old Rus settlements of the Steppe Dniester territory permits attributing their origin to migration of ulichs to the south of the Dnieper in the 10th cent. In the course of time (11th-13th cent) the number of inhabitants in those settlements, as well as in other ones in the lower reaches of the Dnieper was supplemented by new migrants from the Middle Dnieper territories. In 11 th- 12th cent, one of such settlements gave rise to the Old Rus town Oleshie.